2006
DOI: 10.1021/ja064062m
|View full text |Cite
|
Sign up to set email alerts
|

One-Electron Reduction of Kinetically Stabilized Dipnictenes:  Synthesis of Dipnictene Anion Radicals

Abstract: The redox behavior of kinetically stabilized dipnictenes, BbtE=EBbt [E = P, Sb, Bi; Bbt = 2,6-bis[bis(trimethylsilyl)methyl]-4-[tris(trimethylsilyl)methyl]phenyl], was systematically disclosed using cyclic voltammetry and theoretical calculations. It was found that they showed reversible one-electron redox couples in the reduction region. The anion radical species of the Bbt-substituted diphosphene and distibene were successfully synthesized by the reduction of the corresponding neutral dipnictenes (BbtP=PBbt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
99
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 41 publications
9
99
0
2
Order By: Relevance
“…8 In addition, ³-bond compounds between heavier group 15 elements (P=P, As=As, Sb=Sb, and Bi=Bi, called dipnictenes) are known to afford stable anion radical species upon chemical reduction, showing their lower LUMO level and stable redox behavior. 9 From a standpoint of using a dipnictene moiety as a ³-spacer, the points of (ii) and (iii) should be clarified and investigated by the construction of bimetallic systems bearing a dipnictene moiety as a ³-spacer. Here again, it is expected that ³-bonds between heavier group 15 elements should be promisingly more effective ³-electron spacers than those of 2nd row elements.…”
mentioning
confidence: 99%
“…8 In addition, ³-bond compounds between heavier group 15 elements (P=P, As=As, Sb=Sb, and Bi=Bi, called dipnictenes) are known to afford stable anion radical species upon chemical reduction, showing their lower LUMO level and stable redox behavior. 9 From a standpoint of using a dipnictene moiety as a ³-spacer, the points of (ii) and (iii) should be clarified and investigated by the construction of bimetallic systems bearing a dipnictene moiety as a ³-spacer. Here again, it is expected that ³-bonds between heavier group 15 elements should be promisingly more effective ³-electron spacers than those of 2nd row elements.…”
mentioning
confidence: 99%
“…The 29 Si NMR spectrum of 1 in C 6 D 6 showed a characteristic signal at 70.6 ppm, which is in the typical range for silicon atoms within a double bond [δ Si (tetraaryldisilenes): 53 66 ppm; δ Si (tetraalkyldisilenes): 90 103 ppm]. 9d The 1 H NMR spectrum of 1 in C 6 D 6 exhibited a pair of pseudo triplet peaks at 3.80 and 3.98 ppm, which should be assigned to the protons of the cyclopentadienyl (Cp) rings.…”
Section: The Synthesis Of D π Electron Systems Withmentioning
confidence: 99%
“…We have also reported that these heavier dipnictenes can be reduced by Li metal to give the corresponding anion radical species. 29 Hence, these π bonds between heavier group 15 elements should be able to work as effective π spacers between transition metal moieties. The simplest conceivable model compound for 1,2 bis(Fc)diphosphenes is Fc P P Fc, i.e.…”
Section: Design and Synthesis Of Bulky Fc Groups: Steric Protection Fmentioning
confidence: 99%
See 2 more Smart Citations